Developing an Algebra Textbook Based on Problem Solving to Improve Student' Learning Achievement - Lusiana, Restu; Andari, Tri (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
Students' mathematics learning achievement is influenced by many factors, one of which is the learning media used. The textbook is one alternative learning media. The textbook used previously was not focused on problem-solving, so that this development research aims to produce a textbook based on problem-solving in algebra that is valid, effective, and practical. This research uses Gall and Borg development research which is limited to seven steps namely research and information collecting, planning, developing a preliminary form of product, preliminary field testing, main product revisions, main field testing, and dissemination. This research was conducted at the Department of Mathematics Education, Universitas PGRI Madiun. Instruments and data collection used in this study were textbook validation sheets, learning outcomes tests, and student response questionnaire. The results of the research showed that the validation result of the textbook was included in the highly valid criteria (86,74 %), the test results met the criteria of classical completeness (82,75%), and the students' response to the textbook was very high (83,33%). Based on these results, it can be concluded that the algebra textbook based on problem-solving can be used in learning. The results of the application of an algebra textbook based on the problem-solving show an increase in student achievement with an N-Gain value of 0.32.